CONVERSION STUDY OF FERRONICKEL INTO NICKEL MATTE BY ADDING GYPSUM AS A SULFURIZING AGENT AND COAL REDUCTOR AT TEMPERATURES OF 1400Â°C AND 1500Â°C - Tarisa D. Valentina, Sherly
The current demand for nickel is increasing due to its role as one of the main materials for the production of battery cathodes in electric vehicles. The raw material for the cathode material in lithium-ion batteries is nickel sulfate, which is derived from the purification of nickel matte. The production of nickel matte in the industry involves the use of relatively expensive pure sulfur, while in Indonesia, there is a byproduct of the chemical industry called gypsum containing CaSO4 which can be an alternative source of sulfur. Therefore, research has been conducted to convert ferronickel into nickel matte using gypsum and coal. The study aims to investigate the effects of process time, gypsum addition, coal addition, and process temperature on the composition of nickel matte, as well as the use of Al2O3 and MgO crucibles on the resulting slag. Preliminary simulations using the thermodynamic software FactSage 8.2 have been conducted using initial characterization data of ferronickel. Subsequently, materials consisting of 1.5 grams of ferronickel, gypsum as a sulfurization agent at 30%, 60%, and 90% of the ferronickel's weight, and coal at 1 and 2 stoichiometric ratios for gypsum decomposition, were mixed and melted inside a vertical tube furnace for 180 minutes. The melting process was carried out under inert conditions using argon gas at temperatures of 1400°C and 1500°C. The effect of process time was also studied with the addition of 60% gypsum, 1 stoichiometric ratio of coal, and a temperature of 1500°C. The experimental results were analyzed using optical microscopy, Scanning Electron Microscope-Energy Dispersive Spectroscopy (SEM-EDS), and X-Ray Diffraction (XRD). The average metal/matte composition obtained in this experiment is 55.19% Fe, 39.55% Ni, and 5.26% S. Longer process time affects the degree of sulfurization of ferronickel. Increasing gypsum addition leads to a decrease in iron content in the metal/matte, while nickel and sulfur content tend to increase. The composition of the metal/matte with the highest average nickel content is achieved with a 90% gypsum addition for both temperature variations, resulting in 36.77% Fe, 53.03% Ni, and 10.25% S with the addition of 1 stoichiometric ratio of coal, and 35.86% Fe, 53.85% Ni, and 10.3% S with the addition of 2 stoichiometric ratios of coal. Meanwhile, the variations in coal addition to decompose gypsum and temperature did not yield significant differences in the results, indicating that using less coal and lower temperatures are sufficient to achieve a sufficiently high nickel content in the metal/matte. The results of the experiment using different types of crucibles show that the Al2O3 crucible results in high solubility of Al2O3 in the slag, while the MgO crucible results in low solubility of MgO in the slag.